HAK MILIK ATAS ASET DIGITAL DI ERA BLOCKCHAIN: TANTANGAN HUKUM PERDATA TERHADAP NFT, TOKENISASI TANAH VIRTUAL, DAN PERLINDUNGAN PEMILIK DI METAVERSE - Sendi Sanjaya (CV. Lafadz Jaya, 2026)
The development of blockchain technology has given rise to new digital assets such as NFTs and the tokenisation of virtual land in the metaverse, challenging the concept of property rights under Indonesian civil law. This literature review analyses the issues surrounding the recognition of digital assets as “property” under Article 499 of the Civil Code, the duality between token property rights and content copyright, and the challenges of cross-border jurisdiction in law enforcement. Through a normative-legal approach, it was found that a synthesis of the Civil Code, the ITE Law, and the PDP Law can provide basic protection, but requires specific regulations to recognise ‘virtual objects’ as a new legal category. Key recommendations include the enactment of a digital assets law and blockchain-based ADR mechanisms to ensure legal certainty for owners within the metaverse ecosystem.